Evolution and Discovery of Matrine Derivatives as a New Class of Anti-Hepatic Fibrosis Agents Targeting Ewing Sarcoma Breakpoint Region 1 (EWSR1) - Bao, Yunyang; Niu, Tianyu; Zhu, Jingyang; Mei, Yuheng; Shi, Yulong; Meng, Runze; Duan, Qionglu; Zhang, Na; Fan, Tianyun; Wang, Yanxiang; Pang, Yudong; Li, Yinghong; et al. (Journal of medicinal chemistry, 2023)
A series of new tricyclic matrinane derivatives were continuously synthesized and evaluated for their inhibitory effects on genes and proteins related to hepatic fibrosis at the cellular level, including collagen type I α1 chain (COL1A1), α smooth muscle actin (α-SMA), connective tissue growth factor (CTGF), and matrix metalloprotein 2 (MMP-2). Among them, compound 6k exerted an appealing potency and significantly reduced liver injury and fibrosis in both bile duct ligation (BDL) rats and Mdr2 knockout mice. An activity-based protein profiling (ABPP) assay indicated that 6k might directly bind to Ewing sarcoma breakpoint region 1 (EWSR1) to inhibit its function and affect the expression of downstream liver fibrosis-related genes and thus regulate liver fibrosis. These results provided a potential novel target for the treatment of liver fibrosis and powerful information for the development of tricyclic matrinanes into promising anti-hepatic fibrosis agents.